Influence of Implant Tilting and Length on the Biomechanics of Single-Tooth Restoration: A Finite Element Analysis in Atrophic Mandible - Eduardo Anitua; Naiara Larrazabal Saez de Ibarra; Iñigo Morales Martín; Luis Saracho Rotaeche (Dentistry Journal, 2022)
The aim of the present study is to assess by means of finite element models the effect on bone stresses of implant length and tilting in single-unit implant restorations. The factors that were analyzed in this study were implant length (4.5, 5.5, and 10 mm), implant titling (0, 17°, 30°, and 45°), bone type (0/I, II, and III), and loading (immediate and delayed). An axial load of 200 N was applied to the occlusal surface of the prosthesis at a height of 11 mm and the Von Mises equivalent stress in the bone was analyzed. Finite element analysis indicated that the most determinant factor was implant tilting. Tilting the implant by 17° doubled the Von Mises stress received by bone. The highest increase was in the case of implant tilting at 45° (by 1300%). The use of extra-short implants did not produce a significant increase in Von Mises stress in bone. Moreover, the length of the implant did not affect the stress value in bone types I and II. Based on the obtained results, an axially placed short implant would be a better option than titling a standard-length implant to support a crown restoration in an atrophic mandible from a biomechanical point of view.